2018
DOI: 10.1108/pijpsm-12-2016-0172
|View full text |Cite
|
Sign up to set email alerts
|

Examining the extent to which repeat and near repeat patterns can prevent crime

Abstract: Purpose: The paper examines the extent and variation in the estimates to which crime can be prevented using patterns of repeats and near repeats, and whether hotspot analysis complements these patterns.Method: Crime data for four study areas in New Zealand are used to examine differences in the extent of burglary repeat and near repeat victimisation. Hotspots of burglary are also created to determine the extent to which burglary repeats and near repeats spatially intersect hotspots.Findings: The extent of repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 26 publications
2
36
1
1
Order By: Relevance
“…The principle of the NRC is the Knox test, which calculate the difference of observed near repeat crime pairs in a spatio-temporal range with expected number by chance 27 . Recently, researchers try to examine the extent to which near repeat patterns can prevent crime 31,32 . They found that crime hotspot and near repeat crime are not co-located with each other and significant space-time clustering does not necessarily indicate an actionable near repeat problem.…”
Section: Discovering Spatial Interaction Patterns Of Near Repeat Crimmentioning
confidence: 99%
“…The principle of the NRC is the Knox test, which calculate the difference of observed near repeat crime pairs in a spatio-temporal range with expected number by chance 27 . Recently, researchers try to examine the extent to which near repeat patterns can prevent crime 31,32 . They found that crime hotspot and near repeat crime are not co-located with each other and significant space-time clustering does not necessarily indicate an actionable near repeat problem.…”
Section: Discovering Spatial Interaction Patterns Of Near Repeat Crimmentioning
confidence: 99%
“…Sorg et al (2017) explicitly operationalise the three components of optimality modelling (decision, currency and constraints), which no other study does. Direct tests of foraging behaviour either measure the extent of spatio-temporal clustering of crime (Johnson and Bowers, 2004a;Chainey and Silva, 2016;Rey et al, 2012;Townsley and Oliveira, 2015;Chainey et al, 2018;Porter and Reich, 2012), or whether individual offenders tend to return to previously target areas (Bernasco et al, 2015;Porter and Reich, 2012;Hering and Bair, 2014). The distinction between both approaches follows from the type of data available, i.e.…”
Section: Spatio-temporal Clustering Of Crime and Crime-controlmentioning
confidence: 99%
“…The majority of studies rely on recorded crime data by law enforcement agencies or international organisations (Chainey and Silva, 2016;Braithwaite and Johnson, 2015;Johnson et al, 2009a;Johnson and Bowers, 2004a;Johnson and Bowers, 2004b;Rosser et al, 2017;Townsley and Oliveira, 2015;Youstin et al, 2011;Li et al, 2014;Nobles et al, 2016;Wang and Liu, 2017;Chainey et al, 2018;Gerstner, 2018;Rey et al, 2012;Glasner et al, 2018;Yu and Maxfield, 2013). In a number of studies data on cleared offenses were used (Wheeler, 2012;Bernasco et al, 2015;Hering and Bair, 2014;Johnson et al, 2009b;Porter and Reich, 2012), which allowed the researchers to link crime events to individual offenders.…”
Section: Spatio-temporal Clustering Of Crime and Crime-controlmentioning
confidence: 99%
See 2 more Smart Citations